Feminism in Disney’s Snow White Live-Action Movie - Dinda Rahmadani; Meisya Audreyanna; Naya Islah Nabilah; Syamsul Bahri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Feminism is a movement that fights for equality between men and women in all aspects of life, including social, political, and cultural. As one of the most influential media producers, Disney has long been criticized for presenting female characters in traditional and passive roles. The purpose of this study is to identify and analyze the feminist elements found in the film and how they reflect the development of gender equality values. This study uses a qualitative descriptive method with data taken directly from the 2025 live-action film Snow White. The analysis is supported by library research and based on Rosemarie Tong’s (2009) feminist theory, which categorizes feminism into eight types. The data is taken from several pictures, dialogues, monologues from Snow White (2025) movie and then analysis done contextually and theoretically. The findings show that the film most strongly reflects liberal feminism (35%), followed by radical and psychoanalytic feminism (24% each), with smaller portions of socialist, existentialist, and ecofeminism. The film presents Snow White not as a passive princess, but as a thoughtful and independent character who questions gender expectations and asserts her own values.